2‐Hydroxypyridine‐N‐oxide (HOPO): Equivocal in the ames assay. (26th February 2018) - Dobo, Krista L.; Cheung, Jennifer R.; Gunther, William C.; Kenyon, Michelle O.
Abstract : 2‐Hydroxypyridine‐N‐oxide (HOPO) is a useful coupling reagent for synthesis of active pharmaceutical ingredients. It has been reported to be weakly mutagenic in the Ames assay (Ding W et al. [2015 ]: J Chromatogr A 1386:47–52). According to the ICH M7 guidance (2014) regarding control of mutagenic impurities to limit potential carcinogenic risk, mutagens require control in drug substances such that exposure not exceeds the threshold of toxicological concern. Given the weak response observed in the Ames assay and the lack of any obvious structural features that could confer DNA reactivity we were interested to determine if the results were reproducible and investigate the role of potentially confounding experimental parameters. Specifically, Ames tests were conducted to assess the influence of compound purity, solvent choice, dose spacing, toxicity, type of S9 (aroclor vs phenobarbital/β‐napthoflavone), and lot variability on the frequency of HOPO induced revertant colonies. Initial extensive testing using one lot of HOPO produced no evidence of mutagenic potential in the Ames assays. Subsequent studies with four additional lots produced conflicting results, with an ∼2.0‐fold increase in revertant colonies observed. Given the rigor of the current investigation, lack of reproducibility between lots, and the weak increase in revertants, it is concluded that HOPO is equivocal in the bacterial reverse mutation assay. It is highly unlikely that HOPO poses a mutagenic risk in vivo; therefore, when it is used as a reagent in pharmaceutical synthesis, it should not be regarded as a mutagenic impurity, but rather a normal process related impurity. Environ. Mol. Mutagen. 59:312–321, 2018. © 2018 Wiley Periodicals, Inc.